The Common Fixed Point Theorems for Six Self-Mappings with Twice Power Type Φ-Contraction Condition: Feng Gu, Dan Zhang - Team, Support (Thai Journal of Mathematics, 2012)
By using the compatible and weakly compatible conditions of self- mapping pair in metric spaces, we discussed the existence and uniqueness of a common fixed point for six self-mappings with twice power type Φ-contractive condition in complete metric spaces. A new common fixed theorem is obtained, which improves and extends some previous results.